The Sensible Heat Flux in the Course of the Year at Ny-Ålesund, Svalbard: Characteristics of Eddy Covariance Data and Corresponding Model Results. (23rd March 2015) - Jocher, Georg; Schulz, Alexander; Ritter, Christoph; Neuber, Roland; Dethloff, Klaus; Foken, Thomas
Abstract : In this paper we present one year of meteorological and flux measurements obtained near Ny-Ålesund, Spitsbergen. Fluxes are derived by the eddy covariance method and by a hydrodynamic model approach (HMA) as well. Both methods are compared and analyzed with respect to season and mean wind direction. Concerning the wind field we find a clear distinction between 3 prevailing regimes (which have influence on the flux behavior) mainly caused by the topography at the measurement site. Concerning the fluxes we find a good agreement between the HMA and the eddy covariance method in cases of turbulent mixing in summer but deviations at stable conditions, when the HMA almost always shows negative fluxes. Part of the deviation is based on a dependence of HMA fluxes on friction velocity and the influence of the molecular boundary layer. Moreover, the flagging system of the eddy covariance software package TK3 is briefly revised. A new quality criterion for the use of fluxes obtained by the eddy covariance method, which is based on integral turbulence characteristics, is proposed.